Two new Phragmidium species identified on Rosa plants native to China - Yang, Ting; Chang, Wei; Cao, Bin; Tian, Chengming; Zhao, Long; Liang, Yingmei (Phytotaxa, 2015)
Two new Phragmidium species, Phragmidium zhouquensis and Ph. longissima, were identified on two native plants, Rosa omeiensis and R. lichiangensis respectively, during an investigation of the occurrence of rust fungi in western China. Phragmidium zhouquensis is mainly characterized by 3–9-celled teliospores bearing minute verrucae on the surface. Phragmidium longissima differs from other Phragmidium species in that it possesses echinulate urediniospores with a pore membrane at the germ pore. Phylogenetic analyses based on 28S rRNA partial gene sequences revealed that specimens of Ph. zhouquensis and Ph. longissima formed two distinct lineages. Phragmidium longissima is the first Phragmidium species to be identified on R. lichiangensis.